A Comparative Study of Pre- and Post-Operative Refractive Errors in Cataract Surgery- Phacoemulsification Vs. Manual Sics In a Secondary Care Hospital - Abdul Aziz Makayee; Sabreen Hassan; Aafiya Kachru (International Journal of Health and Clinical Research, 2021)
Introduction: Cataract surgery, today is seen as a refractive surgery. So we should be concerned not only to correct the spherical ammetropia, but also the cylindrical. Cataract is the most important and significant cause of bilateral blindness in senile age group, both in India as well as on a global scale. Modern cataract surgeries with intraocular lens (IOL) have become one of the safest, most successful, simple, and consistent and most frequently performed surgeries.Materials and Methods: This prospective observational research design was conducted among cataract patients with age between 40 to 70 years who attended Ophthalmology OPD in Govt Medical College, Baramulla during January 2020 to December 2020. Sample size was calculated based on the study by Cook C et al, proportion of corrected visual acuities as normal in phacoemulsification group was 36% while it was 18% in SICS group during 8 weeks follow up.Results: In this study, 50 patients in group I and 50 patients in group II were operated for cataract by phacoemulsification and manual SICS respectively. The mean age in Phaco group was 60.72±4.31 years while mean in SICS groups was 61.91±5.36 years. Majority patients in Phaco group were males (55%) while in SICS group were females (54%). Almost equal number of cases in both the groups were operated for right and left eyes.Conclusion: Small-incision surgery does not need the capital investment and recurring expenditure of a phacoemulsification machine. Training in phacoemulsification surgery has a steep learning curve than small-incision cataract surgery for ophthalmic surgeons. It is recommended as an alternative procedure to phacoemulsification where the requisite equipment and expertise are not available.